A Clearer Picture: Journalistic identity practices in words and images on Twitter. (26th November 2018) - Lough, Kyser; Molyneux, Logan; Holton, Avery E.
Abstract : As journalists continue integrating social media into their professional work, they wrestle with ways to best represent themselves, their organizations, and their profession. Several recent studies have examined this trend in terms of branding, raising important questions about the changing ways in which journalists present themselves and how these changes may indicate shifts in their personal and professional identities. This study combines a visual content analysis of the images journalists use in their Twitter profiles with analyses of their profile text and tweets to examine how journalists present themselves online with an eye toward individual and organizational branding. Findings indicate journalists choose a branding approach and apply it consistently across their profiles, with most profiles consisting of a professional headshot while notably lacking organizational identifiers such as logos. Journalists also tend to lean toward professional rather than personal images in their profile and header photographs, indicating a possible predilection for professional identity over personal on social media.